Evasão nos cursos técnicos de educação à distância do Instituto Metrópole Digital: um estudo de caso em um polo da região do semiárido nordestino - Lima, Washington Luiz da Silva (Universidade Federal Rural do Semi-Árido, 2019)
The aim of this research was to identify the evasion factors of a technical distance education course - EAD of Instituto Metrópole Digital (IMD) in a semiarid poles of the Northeast, with the purpose of contributing with indicators that increase the opportunities for permanence of the courses. For that, a case study was carried out, based on the data provided by the IMD, as well as a reflection of the theoretical reference referring to the theme. The findings of this study show that the lack of time and the dilemma between finishing a technical course and starting a university course, lack of adaptation to methods used in e-learning, the need to enter the labor market, lack of time make it the main factors for avoidance. Thus, it is indispensable to improve the methodology of teaching in the blended system, student satisfaction survey, mediator teacher and staff to identify the factors that arise and change the practices of student support, in addition to in-service training for professionals to minimize avoidance rates.
Monografia
Keywords: Evasão; Curso técnico; Educação à distância; Instituto Metrópole Digital; Evasion; Technical course; E-learning; Instituto Metrópole Digital; CIENCIAS EXATAS E DA TERRA::COMPUTACAO E INFORMATICA